PENGGUNAAN STRATEGI KNOW-WANT-LEARN (KWL) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI PADA POKOK BAHASAN SISTEM EKSKRESI MANUSIA UNTUK SISWA KELAS XI IPA 2 SMA NEGERI 1 SALO: (Using Know-Want-Learn (KWL) Strategy to Improve Students’ Learning Outcomes of Biology on Human Excretion System at Class XI IPA 2 SMA Negeri 1 Salo) - Khadijah Khadijah (Perspektif Pendidikan dan Keguruan, 2015)
Classroom action research has been done in SMA Negeri 1 Salo on Biology subject, the research object was class XI IPA 2 in the second semester 2012/2013. This study was conducted in an effort to improve students’ learning outcome on Biology with the topic of the human excretion system at class XI IPA 2. The learning model Know-Want-and Learn (KWL) have to be applied after observation and reflection carried out by the researcher. Researcher planned of action based on the results of observations and reflections that have been made through the development of learning-based learning tools Know-Want-and Learn (KWL) consisting of test questions (repeat), observation sheets and lesson plans and other supporting learning device. The learning model Know-Want-and Learn (KWL) consists of three main stages, namely: students know the material, ask students a question, ask the students to learn the material, ask students to discuss the subject material, and asked the students to do the exercise. This study can be completed in 2 cycles of 4 meetings and twice daily tests. Results of research is the observation data and the recapitulation of the test (replications) and recapitulation completeness study shows there has been increased activity of positive student learning in the classroom and increase the mean test (repeats) as well as an increase in classical completeness of cycle 1 to cycle 2. Activity of students during the process learning is observed by the observer as the data for evaluation and reflection. Recapitulation mean test (replications) and mastery learning derived from the value of the daily tests daily tests I and II. Based on the results of this study concluded that the application of learning models Know-Want-and Learn (KWL) in class XI IPA 2 SMA Negeri 1 Salo is able to improve learning outcomes Biology subjects indicated by the mean test (replications) and classical completeness in every cycle.